Strategi Bertahan Usaha Mikro Kecil Menengah (UMKM) dalam Menghadapi Krisis Ekonomi Global - Mohammad Afrizal Miradji; Siti Masruroh; Nuzulul Arifah Magfiroh; Nabillah Amrista Putri; Alifia Anindita Putri; Sherly Widya Mei (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in maintaining economic stability, especially during global economic crises that reduce purchasing power. This study examines MSME survival strategies through a case study of Cirayeum, a micro-scale culinary business producing chicken-filled cireng. Using a descriptive qualitative case study approach, data were collected through observations, interviews, and financial documentation. The results show that Cirayeum survives through product innovation, flexible sales formats (ready-to-eat and frozen), and affordable pricing. Financial analysis indicates effective cost control, accurate cost calculation, and positive profit and return on investment. SWOT analysis highlights product quality and low costs as strengths, while competition and raw material price fluctuations remain key challenges. Overall, adaptive strategies are crucial for MSME resilience amid economic uncertainty.